A Study to Assess the Level of Knowledge on Home Management of Diarrhea among Mothers. (Indian Journal of Public Health Research & Development, 2020)
Diarrhea is one of the most common manifestations of illness in infants and children. Diarrhea is a symptomof variety of conditions, and it constitutes one of the main causes of morbidity and mortality among infantsand throughout the world1. The resent study was to assess the level of knowledge on home managementof diarrhea among the mothers”and the objectives were to assess the existing level of knowledge on homemanagement of diarrhea among mothers and to associate the level of knowledge on home managementof diarrhea with their selected demographic variables. Non experimental –descriptive research study wasconducted. The study sample consisted of total 100 mothers of under five children. The study finding showsthat majority of the mothers were having inadequate knowledge and most of the mothers were havingmoderate knowledge and no mother were having adequate knowledge. The mean value of knowledge scorewas 9 and the standard deviation was 3. The study findings also shows that there is no significant associationbetween the demographic variables such as (age, education, income, type of family, residence, source ofinformation) and the level of knowledge of mothers regarding home management of diarrhea at p
Keywords: Level of knowledge, home management of diarrhoea, mothers